A systematic review on the use of healthcare services by undocumented migrants in Europe - Marjolein Winters; Bernd Rechel; Lea de Jong; Milena Pavlova (BMC, 2018)
Abstract Background Undocumented migrants face particular challenges in accessing healthcare services in many European countries. The aim of this study was to systematically review the academic literature on the utilization of healthcare services by undocumented migrants in Europe. Methods The databases Embase, Medline, Global Health and Cinahl Plus were searched systematically to identify quantitative, qualitative and mixed methods studies published in 2007-2017. Results A total of 908 articles were retrieved. Deletion of duplicates left 531. After screening titles, abstracts and full texts according to pre-defined inclusion and exclusion criteria, 29 articles were included in the review. Overall, quantitative studies showed an underutilization of different types of healthcare services by undocumented migrants. Qualitative studies reported that, even when care was received, it was often inadequate or insufficient, and that many undocumented migrants were unfamiliar with their entitlements and faced barriers in utilizing healthcare services. Conclusions Although it is difficult to generalize findings from the included studies due to methodological differences, they provide further evidence that undocumented migrants in Europe face particular problems in utilizing healthcare services.